Exploitation of glucose catabolic gene fusions to investigate in situ expression during Pseudomonas-plant interactions - Rice, O.; Miller, S.; Morrissey, J.; O'Gara, Fergal (Springer, 2012)
Successful exploitation of bacterial inoculants in agriculture requires that the inoculant can colonize the crop rhizosphere and then express the gene(s) of interest. This study focuses on two glucose-metabolizing genes that are associated with the inorganic phosphate solubilization phenotype of Pseudomonas fluorescens: gcd, which encodes glucose dehydrogenase, and pqqB, which encodes a cofactor required for Gcd activity. Tn5-lux-gene fusions were created to assess the expression of these genes in situ on roots of two maize hybrids, DK315 and PR37Y15. Expression was compared to in vitro levels in the presence of root exudates and different carbon sources. Although root exudates from both varieties triggered similar levels of expression in in vitro cultures, there was a marked difference in situ, where significantly higher expression levels of both genes were observed on DK315 roots. This correlates with a higher level of rhizosphere colonization by the inoculant on this hybrid (over PR37Y15) and illustrates the importance of monitoring both colonization and expression levels in tandem. In addition to demonstrating expression of these important genes in the rhizosphere, this study also illustrates that variation can exist between cultivars or varieties and demonstrates a methodology to monitor the expression of genes of interest in the rhizosphere of the selected crop variety on which the inoculant is to be applied.